Stress and positive attitudes towards violent discipline are associated with school violence by Ugandan teachers. (July 2019) - Ssenyonga, Joseph; Hermenau, Katharin; Nkuba, Mabula; Hecker, Tobias
Abstract: Background: Globally, the use of violent discipline methods by teachers to manage child behavior is still highly prevalent despite enactment of laws that prohibit school violence. In the case of Uganda there is a dearth of accurate prevalence statistics on school violence and factors associated with the use of violence by teachers. Objectives: Therefore, the current study examined the prevalence of and attitudes towards violence. The study also explored the association between teachers' stress, positive attitudes towards violence and the use of violent discipline management methods. Methods: A representative sample of 291 teachers and 702 students from 12 public secondary schools in southwestern Uganda responded to anonymous self-administered questionnaires. Data were collected from April to November 2017. Results: Findings indicated that 86.5% of the teachers reported having used violent disciplinary methods on students in the past month while 91.5% of the students reported experiencing violence by teachers. Teachers (88.3%, n  = 256) endorsed positive attitudes towards violent discipline. Teachers' stress was related to higher levels of violent discipline (β = 0.20). This relation was mediated by positive attitudes towards violence (0.06, SE: 0.01, 95%-CI: 0.035–0.092). Conclusions: Our findings indicate that teacher reported stress was associated with their use of violent behavior and positive attitudes and that positive attitudes reduced the association between teachers' stress and violent behavior. Therefore, interventions aiming to reduce violence by teachers may need to integrate effective stress management skills, in addition to nonviolent discipline strategies, and fostering attitudinal change towards the use of violent methods.